Religiusitas dan Dukungan Sosial sebagai Penentu Konsep Diri: Studi Kasus pada Perempuan Korban Perselingkuhan - Eva Fitria Yulianty; Siti Sekar Ayu Fadillah; S Zazirah; Yulina Eva Riany (Society, 2024)
Infidelity is a complex social issue that has profound psychological impacts on its victims. Infidelity does not always involve sexual relationships; it can also manifest as emotional closeness. However, any form of infidelity has the potential to undermine the integrity of a marital bond. While infidelity can occur in both men and women, research identifies men as more likely to engage in such behavior. This study aims to analyze the impact of a husband’s infidelity on a wife’s self-concept. A qualitative phenomenological method was employed. The findings, based on interviews with four participants, reveal that infidelity within a marriage leads to feelings of anger, disappointment, and negative self-perceptions, such as feeling unwanted or unworthy and a loss of motivation to live with enthusiasm. Social support and religiosity were identified as critical factors in rebuilding the self-concept of victims of infidelity. Although religiosity does not instantly eliminate emotional pain, it serves as a significant source of strength, calm, and hope in the process of healing emotional wounds. Recovery from this emotional pain is not an easy process. Social support encompasses assistance in self-acceptance, emotional recovery, and the reconstruction of self-identity. Religiosity fosters self-awareness and reflection, helping individuals shift their focus from worldly concerns to spirituality and ultimate life goals. This facilitates adaptation accompanied by feelings of comfort, tranquility, optimism, and gratitude. Religiosity and social support are perceived as enhancing psychological well-being, providing emotional support, and helping individuals face life’s challenges with greater resilience.